ANALISIS PENGENDALIAN MUTU PETIKAN, KADAR AIR DAN SENSORI TEH HITAM PT PAGILARAN MENGGUNAKAN STATISTICAL PROCESS CONTROL (SPC) - Annisa, Wilda Nur; ., Agus Suyanto (Jurnal Pangan dan Gizi, 2024)
PT Pagilaran is one of the black tea plantation companies in Indonesia. This study aims to determine the quality control of plucking, moisture content, and sensory at PT Pagilaran. The study used descriptive quantitative research with the Statistical Process Control (SPC) method. Quality control of pluckings using Pareto diagrams, obtained data showing that the type of plucking on young leaves has a value less than MS 40%. Control of the type of picking on young leaves has an average percentage of the Pagilaran garden of 32.6%, Andongsili at 34.4%, Kayulandak at 35.4% and the defective shoots are by the standard not exceeding 15%. This has decreased due to the culture related to employee picking not by company standards, the most important thing is to produce a lot of tea without paying attention to the quality of tea, employee salaries are based on the amount of tea picked. Quality control of moisture content using R-Chart and X-Chart diagrams identified that quality control was within control limits. Sensory quality control using Pareto diagrams in the first and second grades has decreased with a value of 3. Factors that cause quality control of tea are humans, methods, materials, environment, machinery, and storage.